Analisis Jumlah Sumur Resapan Berdasarkan Kebutuhan Air Bersih dan Irigasi Kecamatan Kanigoro - Moh. Fahmi Ferdiansyah; Trisno Widodo; Risma Dwi Atmajayani (LPPM Universitas Nahdlatul Ulama Blitar, 2024)
The increase in population and regional development in Kanigoro Subdistrict, Blitar District, has caused environmental changes that impact groundwater availability. To address this issue, infiltration pond planning was conducted using a quantitative method with Capacity-Based Method calculations. Calculation of clean water needs for the next 20 years of projected total discharge with the highest value of Sawentar Village 37,663 l/d. The need for irrigation water using the Blaney-Criddle method in each hectare is 5589416 L/Ha. Planning infiltration wells in Kanigoro Subdistrict is planned with SRB 1 design, with dimensions of 80 cm by 200 cm and dimensions of 70 cm by 150 cm, obtained the capacity of infiltration wells one of which is Minggirsari settlement 0.101531045 m3/s, as well as for Minggirsari rice fields 0.083962657 m3/s, The number of infiltration wells for Sawentar settlement 27 units and 80 units of rice fields. The planning results show that infiltration ponds can reduce the flow rate with an average of 2% in settlements and 4% in rice fields. The total planning of infiltration ponds for the entire Kanigoro sub-district is 19.49% for housing and 47.64% for rice fields.